Keterampilan Proses Sains (KPS) Siswa pada Materi Laju Reaksi Menggunakan LKS Berorientasi KPS - Uci Agustina; Noor Fadiawati; Lisa Tania (Jurnal Pendidikan dan Pembelajaran Kimia, 2017)
This quasi experimental research using the matching only pretest-posttest control group design aimed to describe the effectiveness of Science Process Skills (SPS) oriented students worksheets in increasing students SPS at reaction rate topic. Population in this research was all students of XI IPA at SMA Muhammadiyah 2 Bandar Lampung in 2016/2017 academic year. The sample were obtained by total sampling technique with XI IPA 1 as an experimental class and XI IPA 2 as a control class. The data analysis techniques used in this research were the calculation of pretest value, posttest value, and n-gain of students SPS. The results revealed that the posttest average value of the students in the experimental class was higher than control class. Moreover, the average of students n-gain in experimental class and control class were 0.53 (medium criteria) and 0.30 (medium criteria), respectively. It can be concluded that the SPS oriented students worksheets were effective to improve students SPS.Penelitian kuasi eksperimen dengan desain the matching only pretest-posttest control group design bertujuan untuk mendeskripsikan efektivitas LKS berorientasi KPS dalam meningkatkan KPS siswa pada materi laju reaksi. Populasi dalam penelitian ini adalah siswa kelas XI IPA di SMA Muhammadiyah 2 Bandar Lampung Tahun Pelajaran 2016/2017. Sampel diperoleh dengan teknik sampling total dengan kelas XI IPA 1 sebagai kelas eksperimen dan XI IPA 2 sebagai kelas kontrol. Teknik analisis data yang digunakan dalam penelitian ini menggunakan perhitungan nilai pretes, postes, dan n-gain KPS siswa. Hasil penelitian menunjukkan bahwa nilai rata-rata postes kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Selain itu, rata-rata n-gain siswa kelas eksperimen dan kelas kontrol berturut-turut sebesar 0,53 (kriteria sedang) dan 0,30 (kriteria sedang). Sehingga, dapat disimpulkan bahwa LKS berorientasi KPS efektif dalam meningkatkan KPS siswa.Kata kunci: keterampilan proses sains, laju reaksi, LKS